Wear of End Mills with Carbon Coatings When Aluminum Alloy A97075 High-Speed Processing - Evgeny E. Ashkinazi; Sergey V. Fedorov; Artem K. Martyanov; Dmitry N. Sovyk; Victor G. Ralchenko; Artem P. Litvinov; Artem A. Ershov; Vitaly I. Konov (Metals)
It is recommended to use high-speed milling to maintain an effective material removal rate and the required cutting-edge geometry. However, on the other hand, high speed increases wear, so the surface of the cutters is modified by deposition functional coatings. The wear of end mills made of CTS12D and H10F tungsten carbides during the high-speed processing of aluminum A97075 (B95T1) was compared. To increase the durability of the tools, well-proven technologies for deposition diamond-like and polycrystalline diamond coatings in microwave plasma with different film structures, which were determined by the coating growth conditions, were used. The milling cutter corner was mostly worn out, but the nature of the wear had its characteristics. It was revealed that at a forced cutting mode of about 1000 m/min, cutters made of CTS12D alloy with a nanocrystalline diamond coating with a “cauliflower” structure and with a diamond-like film showed 10% higher resistance. The primary wear mechanism was adhesive. Images of worn cutting edges were obtained using a 3D optical digital image processing system.